Setting up and running a small food business - Fellows, Peter; Axtell, Barrie (Technical Centre for Agricultural and Rural Cooperation, 2001)
This is the first in a series of manuals on small-scale food processing, compiled by contributors from several developing countries. Intended as a practical guide for people starting or operating a food business, it covers a range of topics including: hygiene, equipment, product testing, suppliers and retailers, and financial, production and staff management.